2019
DOI: 10.1590/0103-8478cr20180822
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryos from Phalaenopsis classic Spotted Pink (Orchidaceae) protocorms

Abstract: The aim of the present study was to induce the formation of somatic embryos in protocorms from Phalaenopsis Classic Spotted Pink hybrids at two physiological maturation stages, namely: 80 and 120 days after seed inoculation (DASI). Protocorms were inoculated in ½ MS medium supplemented with 0.1 mg L-1 ANA and 3 mg L-1 TDZ. Protocorms were inoculated 120 days after sowing were more developed at the 15th cultivation day due to the formation of pro-embryogenic structures. It was possible seeing the formation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Since the 30 th day after incubation, the explants of the selected intergeneric hybrid of Phalaenopsis 2166 x Vanda' Saint Valentine' were subjected to 12 hour-exposure to light and another 12 hours in the dark. As a comparison, the explants of Phalaenopsis Classic spotted pink started to form the last globular structure on the 23 rd day, and the embryos began to form coleoptelar (Pereira et al 2019). Meanwhile, direct somatic embryogenesis from leaf explants in Phalaenopsis' Little Steve' revealed that somatic embryos were formed on the 30 th day after explant incubation in the dark (Kuo et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Since the 30 th day after incubation, the explants of the selected intergeneric hybrid of Phalaenopsis 2166 x Vanda' Saint Valentine' were subjected to 12 hour-exposure to light and another 12 hours in the dark. As a comparison, the explants of Phalaenopsis Classic spotted pink started to form the last globular structure on the 23 rd day, and the embryos began to form coleoptelar (Pereira et al 2019). Meanwhile, direct somatic embryogenesis from leaf explants in Phalaenopsis' Little Steve' revealed that somatic embryos were formed on the 30 th day after explant incubation in the dark (Kuo et al 2005).…”
Section: Discussionmentioning
confidence: 98%